2016
DOI: 10.4081/aiol.2016.6266
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Cladocera species from Central America based on subfossil assemblages

Abstract: <p>Cladocera species composition was analyzed in surface sediments of 29 lakes in Central America (Guatemala, El Salvador and Honduras). The material studied was collected with an Ekman grab in autumn 2013 from lakes located in lowland, highland and mountain regions. The study revealed high variability in qualitative and quantitative composition of subfossil Cladocera. A total of 31 Cladocera species (5 planktonic and 26 littoral) were identified, as well as 4 morphotypes that could not be identified (NR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Overall, the lake was shallow, biological productivity was high, and a dense macrophyte cover was present in the bottom of the lake, maintaining relatively clear waters and probably mesotrophic conditions (Alonso ; Wojewódka et al . ). During this time interval the lake was an optimal scenario for the development of dense communities of littoral and substrate‐associated cladocerans and macrophytes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Overall, the lake was shallow, biological productivity was high, and a dense macrophyte cover was present in the bottom of the lake, maintaining relatively clear waters and probably mesotrophic conditions (Alonso ; Wojewódka et al . ). During this time interval the lake was an optimal scenario for the development of dense communities of littoral and substrate‐associated cladocerans and macrophytes.…”
Section: Discussionmentioning
confidence: 97%
“…; Wojewódka et al . ), indicating a substantial deepening and enlargement of the lake. This change was also evidenced by the replacement of submerged macrophytes by floating plants such as Nymphae and Polygonaceae (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nevalainen and Luoto (2010) also reported that many Cladocera species are sensitive to seasonal temperature changes. Zawisza et al (2016) and Wojewódka et al (2016) reported that several studies described strong correlations between pH, conductivity and Cladocera taxa. Bjerring et al (2009) found negative correlations between temperature and chlorophyll-a and several Cladocera taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to sampling, the following physical and chemical parameters of the surface water were recorded: max. depth 2.8 m, Secchi depth 2.8 m, surface water temperature 12.5 C, pH 8.8, conductivity 331 µS m -1 and O 2 content 6.2 mg L -1 (for more details see Wojewódka et al 2016).…”
Section: Methodsmentioning
confidence: 99%